2022
DOI: 10.1155/2022/5625945
|View full text |Cite|
|
Sign up to set email alerts
|

Real-Time Image Defect Detection System of Cloth Digital Printing Machine

Abstract: In order to solve the surface defects such as white silk, spots, and wrinkles on the fabrics in the process of digital printing production, a surface defect detection system for printed fabrics based on the accelerated robust feature algorithm is proposed. The image registration is mainly carried out by the speeded up robust features (SURF) algorithm; the bidirectional unique matching method is used to reduce the mismatch points, realize the accurate registration of the image, and extract the defect informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The mAP of this method is 77%. Sun et al [25] proposed a surface defect detection system for printing fabric based on an accelerated robust feature algorithm. The detection system is used to detect the defects of white silk, spots, and wrinkles on fabric products.…”
Section: Related Workmentioning
confidence: 99%
“…The mAP of this method is 77%. Sun et al [25] proposed a surface defect detection system for printing fabric based on an accelerated robust feature algorithm. The detection system is used to detect the defects of white silk, spots, and wrinkles on fabric products.…”
Section: Related Workmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%